Biology - Peter H Raven (McGraw Hill Education (India) Private Limited, 2013)
This text is up-to-date, beautifully illustrated, and pedagogically sound for the student. They have provided clear, explicitbr>learning objectives, and more closely integrate the text with its media support materials to provide instructors with anbr>excellent complement to their teaching.br>br>Features: br>br>ÃƒÂ¢Ã¢â€šÂ¬Ã,Â¢ This text is up-to-date, beautifully illustrated, and pedagogically sound for the student. They have provided clear,br>explicit learning objectives, and more closely integrate the text with its media support materials to providebr>instructors with an excellent complement to their teaching.br>ÃƒÂ¢Ã¢â€šÂ¬Ã,Â¢ Each chapter begins with an outline of the chapter.Learning outcomes are included for every major topic to helpbr>students see the forest for the trees and focus on the main concepts and relationships of the details being presentedbr>to them.br>ÃƒÂ¢Ã¢â€šÂ¬Ã,Â¢ Inquiry questions are found throughout the text to push the students further in their ability to think scientifically.br>ÃƒÂ¢Ã¢â€šÂ¬Ã,Â¢ End of chapter review questions include Understanding, Applying and Synthesizing levels.br>Table of Contents:br>Part 1: The Molecular Basis of Life br>1--The Science of Biology br>2--The Nature of Molecules br>3--The Chemical Building Blocks of Lifebr>br>Part II: Biology of the Cell br>4--Cell Structure br>5--Membranes br>6--Energy and Metabolism br>7--How Cells Harvest Energy br>8--Photosynthesis br>9--Cell Communication br>10--How Cells Dividebr>br>Part III: Genetic and Molecular Biology br>11--Sexual Reproduction and Meiosis br>12--Patterns of Inheritance br>13--Chromosomes, Matting & the Meiosis-Inheritance br>Connection br>14--DNA: The Genetic Material br>15--Genes and How They Work br>16--Control of Gene Expression br>17--Biotechnology br>18--Genomics br>19--Cellular Mechanisms of Developmentbr>br>Part IV: Evolution br>20--Genes Within Populations br>21--The Evidence for Evolution br>22--The Origin of Species br>23--Systematics and the Phylogenetic Revolution br>24--Genome Evolution br>25--Evolution of Developmentbr>br>Part V: Diversity of Life on Earth br>26--The Tree of Life br>27--Viruses br>28--Prokaryotes br>29--Protists br>30--Green Plants br>31--Fungi br>32--Overview of Animal Diversity br>33--Noncelibate Invertebrates br>34--Coelomate Invertebrates br>35--Vertebratesbr>br>Part VI: Plant Form and Function br>36--Plant Form br>37--Vegetative Plant Development br>38--Transport in Plants br>39--Plant Nutrition and Soils br>40--Plant Defense Responses br>41--Sensory Systems in Plants br>42--Plant Reproductionbr>br>Part VII: Animal Form and Function br>43--The Animal Body and Principles of Regulation br>44--The Nervous System br>45--Sensory Systems br>46--The Endocrine System br>47--The Musculoskeletal System br>48--The Digestive System br>49--The Circulatory System br>50--The Respiratory System br>51--Temperature, Osmotic Regulation and the Urinary br>System br>52--The Immune System br>53--The Reproductive System br>54--Animal Developmentbr>br>Part VIII: Ecology and Behavior br>55--Behavioral Biology br>56--Population Ecology br>57--Community of Ecology br>58--Dynamics of Ecosystems br>59--The Biosphere br>60--Conservation Biology